Non-coding autoimmune risk variant defines role for ICOS in T peripheral helper cell development - Kim, Taehyeung; Martínez-Bonet, Marta; Wang, Qiang; Hackert, Nicolaj; Sparks, Jeffrey A.; Baglaenko, Yuriy; Koh, Byunghee; Darbousset, Roxane; Laza-Briviesca, Raquel; Chen, Xiaoting; Aguiar, Vitor R. C.; Chiu, Darren J.; et al. (Nature Communications, 2024)
Fine-mapping and functional studies implicate rs117701653, a non-coding single nucleotide polymorphism in the CD28/CTLA4/ICOS locus, as a risk variant for rheumatoid arthritis and type 1 diabetes. Here, using DNA pulldown, mass spectrometry, genome editing and eQTL analysis, we establish that the disease-associated risk allele is functional, reducing affinity for the inhibitory chromosomal regulator SMCHD1 to enhance expression of inducible T-cell costimulator (ICOS) in memory CD4+ T cells from healthy donors. Higher ICOS expression is paralleled by an increase in circulating T peripheral helper (Tph) cells and, in rheumatoid arthritis patients, of blood and joint fluid Tph cells as well as circulating plasmablasts. Correspondingly, ICOS ligation and carriage of the rs117701653 risk allele accelerate T cell differentiation into CXCR5-PD-1high Tph cells producing IL-21 and CXCL13. Thus, mechanistic dissection of a functional non-coding variant in human autoimmunity discloses a previously undefined pathway through which ICOS regulates Tph development and abundance.
Gesehen am 06.08.2024